Answer:
The vertex form of the given equation is f(x) = 2(x-4)²+(-27) where vertex is (4,-27).
Explanation:
We have given a quadratic equation in standard form.
y= 2x²-16x+5
We have to rewrite given equation in vertex form.
y = (x-h)²+k is vertex form of equation where (h,k) is vertex of equation.
We will use method of completing square to solve this.
y = 2(x²-8x)+5
Adding and subtracting (-4)² to above equation, we have
y = 2(x²-8x+(-4)²)+5-2(-4)²
y = 2(x-4)²+5-2(16)
y = 2(x-4)²+ 5 -32
y = 2(x-4)²-27
Hence, The vertex form of the given equation is f(x) = 2(x-4)²+(-27) where vertex is (4,-27).